What international accounting standards (IAS) bring about to the financial statements of Greek listed companies: the case of the Athens stock exchange - Bellas, Athanasios; Tountas, Kanellos; Papadatos, Konstantinos (SPOUDAI Journal of Economics and Business, 2007)
The aim of the present study is to investigate the repercussions of the accounting changeover from the Greek Accounting Standards (GAS), to the International Accounting Standards (IAS) in relation to the published financial statements of Greek listed companies for the year 2004. The results show that tangible assets, fixed assets, and total liabilities record significantly higher prices under the IAS. Furthermore, it was recorded that, in opposition to the net income after taxes, the book value appears to play a more significant role under the IAS, compared to that under the GAS. There is also evidence that the adjustments of GAS to net income improve incremental value relevance, while the adjustments of GAS to book value do not improve it. JEL Classification: M41